STRESS-PROTECTIVE AND ANTIOXIDANT EFFECT OF HUMULUS LUPULUS DRY EXTRACT AT CHRONIC EMOTIONAL STRESS - Ya. G. Razuvaeva; A. A. Toropova; N. S. Kukharenko; S. M. Nikolaev; I. P. Ubeyeva (Acta Biomedica Scientifica, 2014)
Stress-protective and antioxidant effects of Humulus lupulus dry extract were studied in experiments on white Wistar rats at prolonged emotional stress. It has been established that the H. lupulus dry extract had stress-protective effect, reducing the manifestation of degenerative catabolic changes in the internal organs of white rats in chronic emotional stress. The antistress activity of Humulus lupulus dry extract is caused by the pronounced antioxidant activity. On the background of the test extract introduction the MDA content decreased and the activity of catalase, SOD and the GSH content in the blood increased.